2020
DOI: 10.1088/1742-6596/1665/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of ß-glucan Extract from Oyster Mushroom (Pleurotus ostreatus) on Expression of Serum Malondialdehyde in Sprague dawley Rats Induced by HFHF Diet

Abstract: The obesity prevalence in the world continues to increase yearly, which further cause clinical problems related to metabolic syndrome and lipid peroxidation. This study aims to determine the effect of ß-glucan extract from oyster mushrooms on lipid peroxidation markers, namely serum MDA levels in rats. Therefore, Sprague dawley rats were divided into four groups, namely the KN group, which was fed with AIN-93M standard diet, the KP group was given the AIN-93M modified HFHF diet, the PI group was fed with AIN-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…Mushroom family has been found to contain vitamin C and selenium that plays important role in antioxidant functions (Bederska-£ojewska et al 2017, Mahfuz andPiao 2019). This observation was contradictory to that reported by Yunita et al (2020) who observed an increased in serum MDA levels when ß-glucan extract of oyster mushroom was used. Therefore, PO extract route of administration in the present study is effective and will allow ease of absorption of these polyphenolic compounds (Qing et al 2020) by the intestine thereby reaching the plasma and marked organs (Giannenas et al 2011) easily to exhibit its antioxidant effect.…”
Section: Resultscontrasting
confidence: 99%
“…Mushroom family has been found to contain vitamin C and selenium that plays important role in antioxidant functions (Bederska-£ojewska et al 2017, Mahfuz andPiao 2019). This observation was contradictory to that reported by Yunita et al (2020) who observed an increased in serum MDA levels when ß-glucan extract of oyster mushroom was used. Therefore, PO extract route of administration in the present study is effective and will allow ease of absorption of these polyphenolic compounds (Qing et al 2020) by the intestine thereby reaching the plasma and marked organs (Giannenas et al 2011) easily to exhibit its antioxidant effect.…”
Section: Resultscontrasting
confidence: 99%
“…A comparison of main peaks of the FTIR spectra of A. bisporus and P. ostreatus is given in Table 1. A similar FTIR spectra has been obtained by other authors [34][35][36] about the structure of β-glucan.…”
Section: Ftir Analysissupporting
confidence: 79%
“…The β-glucan from the oyster mushroom extract was produced based on the previous study. 21 All experimental procedures have been approved by The Research Ethics Committee of the Faculty of Medicine, Universitas Brawijaya, Indonesia (136/EC/KEPK/07/2020).…”
Section: Animals and Dietmentioning
confidence: 99%